Super Twisting Disturbance Observer-Based Fixed-Time Sliding Mode Backstepping Control for Air-Breathing Hypersonic Vehicle - Yunjie Wu; Fei Ma; Xiaocen Liu; Yueyang Hua; Xiaodong Liu; Guofei Li (IEEE Access)
This paper investigates the velocity and altitude tracking control problem for air-breathing hypersonic vehicle (AHV) under external disturbances and uncertainties. An improved smooth super-twisting based disturbance observer (SSTDOB) is proposed to estimate the unknown external disturbances. With the assistance of SSTDOB, an effective fixed-time sliding mode backstepping control (FSMBC) is designed to guarantee the tracking errors converge to a small neighbor of the origin. Meanwhile, a fixed-time tracking differentiator (FTD) is employed to estimate the virtual control inputs, which can eliminate the differential explosion problem. The overall stability of the closed-loop system is analyzed by utilizing Lyapunov stability theory. Simulation results demonstrate the effectiveness of the composite method.